Comparaison de diagnostics par scintigraphic hépatique à l’aide d’un scanner et d’une caméra à rayons gamma et leur corrélation avec quelques tests de la fonction hépatique - Rissanen, P. M.; Patomäki, L. K. (Nuklearmedizin - NuclearMedicine, 1969)
The livers of 154 patients have been studied with the aid of scintigraphy, done in succession with a scanner and a gamma camera, with the purpose of determining which of the two machines provided the more reliable results. The scanner alone gave 40% and the gamma camera alone 39% but both together 45% positive findings. They were consistent in 85% of the cases. A laparotomy or autopsy was performed on 23 patients within one month after scintigraphy. In two of these cases, a negative scintigram had been obtained despite metastases in the liver; no false positives were found. The correlation of alkaline phosphatase, 5-nucleotidase and GOT with the presence of liver metastases was found to be rather moderate. By using both machines together it is possible to arrive at slightly better results than by using either of them alone.